Neurosains- Spiritualitas dan Pengembangan Potensi Kreatif - Imam Hanafi (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
Neuroscientists in Indonesia now actively conduct researches on functions of brains relating to spiritual activity of humans. The results show that brains maintaining human activities have significant role in the spiritual activities and creative potentiality. Based on the facts, I then tend to elaborate how the spiritual activities seen from neuroscientific perspective simply and easily to be understood. Therefore, it is important to study how to maximize the relationship of the potentiality and the spirituality to create creative humans with strong controls.